2010
DOI: 10.2174/1874192401004010127
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing in Patients with Chronic Heart Failure: Prognostic Comparison from Peak VO2 and VE/VCO2 Slope

Abstract: Background:Cardiopulmonary exercise testing with ventilatory expired gas analysis (CPET) has proven to be a valuable tool for assessing patients with chronic heart failure (CHF). The maximal oxygen uptake (peak V02) is used in risk stratification of patients with CHF. The minute ventilation-carbon dioxide production relationship (VE/VCO2 slope) has recently demonstrated prognostic significance in patients with CHF. Methods:Between January 2006 and December 2007 we performed CPET in 184 pts (146 M, 38 F, mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 27 publications
3
60
2
2
Order By: Relevance
“…A previous meta-analysis did not analyze change in V E /VCO 2 slope in HFpEF patients [16]. A previous report established a strong prognostic relationship between peak VO 2, V E /VCO 2 slope and mortality in heart failure patients with reduced systolic function [34]. Our analysis showed maximum heart rate to be higher after exercise training; the resultant increase in maximal cardiac output would at least partially explain why peak VO 2 improved with training.…”
Section: Discussionmentioning
confidence: 47%
“…A previous meta-analysis did not analyze change in V E /VCO 2 slope in HFpEF patients [16]. A previous report established a strong prognostic relationship between peak VO 2, V E /VCO 2 slope and mortality in heart failure patients with reduced systolic function [34]. Our analysis showed maximum heart rate to be higher after exercise training; the resultant increase in maximal cardiac output would at least partially explain why peak VO 2 improved with training.…”
Section: Discussionmentioning
confidence: 47%
“…Previous analyses of exercise training intensity in heart failure patients have shown that high-intensity training may produce the largest changes in peak V O 2 [12,13] with a liner decrease in effect size with decreasing exercise intensity. Greater peak V O 2 values are associated with reduced mortality and morbidity in heart failure [20]. Intuitively improved cardiorespiratory fitness has been shown to correlate with improved quality of life in heart failure patients [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of variables have been assessed for their diagnostic and prognostic capabilities, with hopes they will portend clinically valuable information [7][8][9][10][11][12][13][14][15]. Moreover, there has been a growing awareness of the additional benefit of applying multivariate scores to evaluate HF patients [14,16].…”
Section: Introductionmentioning
confidence: 99%